2019
DOI: 10.37358/rc.19.10.7575
|View full text |Cite
|
Sign up to set email alerts
|

A Fugacity Based Model for the Assessment of Pollutant Dynamic Evolution of VOCS and BTEX in the Olt River Basin (Romania)

Abstract: An important tributary of the Danube River, the Olt River, was characterized in its middle and lower catchment in terms of volatile organic compounds (1,2 -dichloroethane and perchlorethylene) and volatile aromatic hydrocarbons (benzene, toluene and xylene isomers) to better assess their transfer in the environmental compartments (air, water, sediment and biota). A fugacity based calculation model was applied to establish the bio-concentration factors (BCFs) that relates the compounds concentration from sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…For example, total BTEX concentrations were reported to be 106 µg/m 3 in ambient air (Ren-Wu, Taiwan) and 0.573 µg/L in rain (Yokohama, Japan). A fugacitybased model developed by Iordache et al [1] also indicated the potential of BTEX transfer from point sources such as wastewater discharges into the environment. Their model highlighted the trend of volatile organic compound transfer in the air, which may require a control of these emissions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, total BTEX concentrations were reported to be 106 µg/m 3 in ambient air (Ren-Wu, Taiwan) and 0.573 µg/L in rain (Yokohama, Japan). A fugacitybased model developed by Iordache et al [1] also indicated the potential of BTEX transfer from point sources such as wastewater discharges into the environment. Their model highlighted the trend of volatile organic compound transfer in the air, which may require a control of these emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that epoxy resins, which are included in the list of occupational toxins, may be involved in the onset of SSc ( 17 , 18 , 20 ). Not only occupational exposure to toxins poses a risk, but also constant or accidental pollution through water and air contamination with halogenated compounds and aromatic hydrocarbons, such as benzene, xylene and toluene ( 21 ). The study on volatile aromatic hydrocarbon toxicity performed by Niculescu and colleagues on laboratory mice reveals some interesting facts.…”
Section: Introductionmentioning
confidence: 99%
“…Classification of pesticides can be achieved depending on their chemical nature (e.g. organic and inorganic), target organism, action timing of their application, the mode of action and degree of their toxicity [6][7][8][9].Organic pesticides, of which the most commonly used are carbamates, triazines, neonicotinoids, pyrethrins, organochlorines, guanophosphates, phenylureas and others, contain carbon in their molecular structure [10]. Inorganic pesticides have mineral derivatives in their composition such as lime, sulfur, antimony, cadmium or lead, which lead to their accumulation of toxic deposits in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic pesticides have mineral derivatives in their composition such as lime, sulfur, antimony, cadmium or lead, which lead to their accumulation of toxic deposits in many cases. A very important aspect is the identification and quantification of pesticide residues and other toxic components in foodstuffs as a crucial part of controlling food safety and public health [6,[11][12][13]. Numerous investigations have been made on various processed food, dairy products, meat, plant products, seeds, vegetables, fruits, as well as in the soil in rural areas, monitoring a wide range of pesticides such as DDT, lindane isomers, endosulfan, cyclodiene and methoxychlor.…”
Section: Introductionmentioning
confidence: 99%